PENGARUH ARUS KAS BEBAS, KONSERVATISME AKUNTANSI, DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - CINDY AGUSTINE; ARWINA KARMUDIANDRI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This research aims to prove whether free cash flow, dividend policy, financial leverage, accounting conservatism, tax avoidance, firm size, return on asset, and sales growth can influence the practice of earnings management. Earnings management is an effort by a company to adjust its financial statements to achieve specific goals, such as attracting investors, meeting performance targets, or reducing tax liabilities. The population of this research comprises manufacturing companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The population that met the criteria consisted of 41 companies, with a total of 121 data points. The method used in this research is purposive sampling and data analysis was conducted using multiple resgression analysis. The results of the research indicate that the independent variables of free cash flow, dividend policy, financial leverage, accounting conservatism, return on assets, and sales growth have an effect on the earnings management. However, other independent variables such as tax avoidance and firm size do not affect earnings management.